How to combat NEET? Evidence from Austria - Dennis Tamesberger; Heinz Leitgöb; Johann Bacher (Intereconomics, 2014)
The number young people not in education, employment or training (NEET) has been rising since the beginning of the economic and financial crisis in 2008. This article contributes to the discussion about the reduction of the NEET rate by addressing the questions: Which structural factors can explain differences in the NEET rates among Austrian federal states? What causes an increased or reduced NEET risk at the individual level? What are the key factors for an exit from a NEET situation?
Keywords: 330; Jugendarbeitslosigkeit; Arbeitsmarktpolitik; Teilstaat; Österreich